Whole Plant Approaches to Therapeutic Use of Artemisia annua L. (Asteraceae) - Weathers, Pamela; Reed, Kirsten; Ogwang, Patrick Engeu (rtemisia annua - Pharmacology and Biotechnology, 2013)
Long used as a therapeutic tea by the Chinese to treat fever, Artemisia annua is more recently being studied and used for eventual treatment for not only malaria, but also many other diseases. This chapter describes studies using in vitro systems, animal models, and humans to evaluate use of not only combinations of pure compounds from the plant, but also tea infusions and the dried leaves of the plant.
Keywords: Artemisinin Combination Therapy; Parasite Clearance; Antiplasmodial Activity; Artemisinin Content; Trophozoite Stage